GENETIC STUDY OF THE TASTE OF PHENYLTHIOCARBAMIDE (PTC) TRAIT IN WASIT PROVINCE POPULATION - Firas Rahi Alhachami; Jinan Tuma Sabah (European Science Publishing, 2025)
The taste of PTC substance is one of the human traits that distinguishes people into tasters and non-tasters, controlled by a single gene (TAS2R38). The current study aimed to determine the genetic distribution of this trait in the community of Wasit Governorate, Iraq, and whether there is a deviation from the normal proportions of the trait. A sample of 500 students of both sexes from Wasit University students, aged between 19-25, were subjected to examination using PTC strips. The study showed that the number of tasters exceeds the number of non-tasters (345 and 155, respectively), and that females are more than males, with a significant difference (p.0.374). the homozygotes recessive (tt) which represented as q and dominants homozygote was represented as p in Hardy Weinberg equilibrium, and the allele frequency of q (t) was 0.211 and p (T) was 0.330 and according to Hardy Weinberg equilibrium, the heterozygotes are represented by the 2pq were (0.480).
Keywords: Taste of Phenylthiocarbamide, human traits, single gene (TAS2R38).